Efektivitas Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi Linn) sebagai Bahan Pembersih Saluran Akar Gigi (The Effectiveness of Wuluh Starfruit (Averrhoa bilimbi Linn) Leaf Extract as Root Canal Cleaner) - Amalia Dara N; Ira Widjiastuti; Laksmiari Setyowati (Universitas Airlangga, 2016)
Background: Preparation is one of the stages in endodontic treatment that always produce debris as a result of intrumentation on root canal walls. Debris consist of organic and inorganic materials. Debris will impede the penetration of disinfection materials and reduce attachment of the root canal filling material, therefore needed root canal irrigant which can remove the debris. Wuluh starfruit leaf extract (Averrhoa bilimbi Linn) contain various active compound, such as saponin. Saponin act as “surfactants” which can remove the debris. Purpose: This study was to determine the cleaning effectiveness concentration of wuluh starfruit leaf extract which can clean the root canal walls from debris. Method: Twenty five first premolar human teeth with straight single roots were randomized into five groups in which each group consist of five teeth. Those teeth instrumented with K-file and irrigated as follows: Group 1 (control) used aquadest as irrigant, group 2 used extract 5%, group 3 used extract 10%, group 4 used extract 15%, and group 5 used extract 20%. Then, those teeth were split horizontally and longitudinally in 1/3 apex. After that, the apical third of root canal walls were observed by using scanning electron microscope (SEM). Result: There were significant differences between each group (p<0,05). Group 4 and 5 had smallest median score that was 1. Saponin in wuluh star fruit leaf extract 15% has been reach critical micelle concentration (CMC). Conclusion: Wuluh starfruit leaf extract 15% effective for cleaning root canal walls from debris.